A Novel PCCA Mutation in a Patient With Late-Onset Propionic Acidemia Identified by Genetic Diagnosis Panel - Wang, Yanyun; Sun, Yun; Jiang, Tao (Frontiers in Pediatrics, 2018)
Background: Propionic acidemia (PA) is an extremely rare autosomal recessive disorder which is caused by the deficiency of propionyl-CoA carboxylase (PCC) and associated with pathogenic variants in PCCA or PCCB gene. Case Report: Detection of PA in neonates is possible using Propionyl carnitine (C3) analysis by tandem mass spectrometry (MS/MS) in dried blood spots (DBS). Here we report one patient with PA. C3 in this case was normal in the initial screening and recall check and only manifested as the slightly increase of C3/C2, 3-hydroxypropionate in urine was only slightly elevated. Then two pathogenic mutations (c.802C>T/c.827delG) were detected in the PCCA gene by Genetic diagnosis panel. Among them, the variation rs774738181 (c.802C>T) was present on the dbSNP database which appeared to be “Likely pathogenic” in GenBank dbSNP (100915068). c.827delG was a novel frameshift mutation, leading to p.Gly276ValfsX46 mutation of amino acid sequence in PCCA. The patient underwent 1 year of follow-up, had total of 7 times and remain asymptomatic whose blood ammonia and liver function were normal. When the child was 1 year of age (in May of 2017), C3 and 3-Hydroxypropionate sudden elevated significantly, that proved pathogenicity of c.802C>T and c.827delG. Conclusion: Two novel mutations (c. 802C>T and c.827delG) in PCCA gene may be associated with late-onset PA, expanding its mutational spectrum. Maybe there is relation between the severity of propionyl-CoA carboxylase (PCC) activity defects and different genotypes.